Penerapan Prinsip Diversi terhadap Pelindungan Hukum Anak Pelaku Tindak Pidana : (Studi Kasus Pengadilan Negeri Medan) - Putri Apriani Harahap; Ramsul Nababan; Majda El Muhtaj (Universitas 17 Agustus 1945, 2024)
This study aims to find out the application of the principle of diversion in the cases of children of criminal offenders in the Medan District Court, as well as to find out the obstacles and obstacles faced in its application. This study uses a normative-empirical legal approach with qualitative methods and case studies. The results of the study show that the principle of diversion is applied to provide optimal legal protection for children involved in criminal acts. Diversion is implemented from the investigation stage to the court, with a focus on shifting case resolution from the formal path to a more humane and rehabilitation-based restorative approach. Factors that contribute to the application of diversion include the type of crime, the involvement of the victim's family in mediation, and the willingness of all parties to reach a peace agreement. Diversion is easier to apply to misdemeanors, while more serious cases often face obstacles in reaching an agreement.